Pandangan Ulama Kota Medan Tentang Pelaksanaan Iddikhar Daging Qurban Di Rumah Zakat Medan-Sumatera Utara - Hubbul Wathan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
The research is empirical legal research also known as sociological and non-doctrinal legal research. It is called as an empirical legal research because it studied legal problem empirically. The research data classified into two kinds: primary and secondary. Both data obtained through interview, observation and documen study. The research concluded that the ulama of Medan agreed on saving sacrificed meat legal status as mubah as it is socially needed. Ulama of Medan also agreed on saving meat legal status as practiced in Rumah Zakat Medan as ubah. The ulama agreement also mean their agreement on legal status of making the meat Superqurban cornet and distributed widely in longer time.